La Armada Argentina en la represión transnacional contra disidentes políticos durante el terrorismo de Estado - Facundo Fernández Barrio (Nuevo mundo - Mundos Nuevos, 2024)
This paper investigates the participation of the Argentine Navy in the repression of political dissidents abroad during State terrorism. Based on a historical reconstruction of the extraterritorial operations that involved the Navy, one of the three military forces that played a leading role in the last Argentine dictatorship (1976-1983), the paper questions the conditions and characteristics of its performance in transnational repression. It is hypothesized that the Navy developed an increasing degree of influence and autonomy in the deployment of the Argentine repressive apparatus beyond national borders. This type of development, observable in the case investigated, suggests a general key of analysis for studies on transnational repression: just as the action of the repressive agencies within the national territory was neither monolithic nor unidirectional, their cross-border action acquired a similar dynamic, characterized by a margin of relative autonomy of the forces involved, although without deviating from the strategic objective of persecuting political dissidents.